2013
DOI: 10.1007/s00213-013-3136-3
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent effects of haloperidol on glutamine and GABA homeostasis and astrocyte activity in the rat brain

Abstract: Rationale Schizophrenia is a severe, persistent, and fairly common mental illness. Haloperidol is widely used and is effective against the symptoms of psychosis seen in schizophrenia. Chronic oral haloperidol administration decreased the number of astrocytes in the parietal cortex of macaque monkeys (Konopaske et al. Biol Psych, 2008). Since astrocytes play a key role in glutamate metabolism, chronic haloperidol administration was hypothesized to modulate astrocyte metabolic function and glutamate homeostasis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 68 publications
0
8
0
2
Order By: Relevance
“…Similarly, Kegeles et al (19) found no difference when they compared unmedicated to medicated patients or controls in the dorsolateral prefrontal cortex (11,16). The animal literature shows either no change (30)(31)(32)(33) or increases in GABA levels in selected areas (32)(33)(34)(35)(36) or in GAD 67 expression in the cortex (37,38) for exposures to antipsychotics ranging from 21 days to 6 months (37,38). Exploratory analyses did not reveal an association between metabolite levels and symptoms in treated or untreated patients for the anterior cingulate voxel.…”
Section: Are Gaba Levels Altered In Unaffected Siblings Of Patients Wmentioning
confidence: 93%
“…Similarly, Kegeles et al (19) found no difference when they compared unmedicated to medicated patients or controls in the dorsolateral prefrontal cortex (11,16). The animal literature shows either no change (30)(31)(32)(33) or increases in GABA levels in selected areas (32)(33)(34)(35)(36) or in GAD 67 expression in the cortex (37,38) for exposures to antipsychotics ranging from 21 days to 6 months (37,38). Exploratory analyses did not reveal an association between metabolite levels and symptoms in treated or untreated patients for the anterior cingulate voxel.…”
Section: Are Gaba Levels Altered In Unaffected Siblings Of Patients Wmentioning
confidence: 93%
“…Over the last year or so, a number of papers in Psychopharmacology have examined the effects of psychotropic drugs on metabolic function and other aspects of physical health (Yan et al 2013;Amrami-Weizman et al 2013;Vieweg et al 2013;Konopaske et al 2013;Joshi et al 2013;Santarelli et al 2013;Kiyatkin 2013;Ou et al 2013;Ogasa et al 2013;Davey et al 2012;Jassim et al 2012;Kim et al 2013). Three papers in this issue extend this to address aspects of metabolic function in patients with mental disorders (Amrami-Weizman et al 2013;Sagud et al 2013;Hu et al 2013).…”
mentioning
confidence: 99%
“…Long-term exposure to antipsychotic drugs might alter the disposition of glutamate and glutamine and affect astrocyte metabolism as suggested by an MRS study in rats. 4 Because pathologic changes have been reported 5 in schizophrenia in the astrocytes, which contain the bulk of glutamine, it may be hazardous to extrapolate from the glutamine disposition in normal brains to that observed in the brains of individuals with schizophrenia. Even accepting the interpretation of increased neurotransmitter glutamate release in schizophrenia, this increase might be compensating for the approximately 30% reduction in glutamatergic synapses as evidenced by dendritic spine loss on pyramidal neurons documented in Golgi studies 6 in schizophrenia.…”
mentioning
confidence: 99%